PENERAPAN PEMBELAJARAN BERDIFERENSIASI DENGAN ALAT PERAGA BALOK ALJABAR UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Setiawati, Erna; Setianingsih, Rini; Kristanti, Dewi (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2025)
Students frequently receive grades that fall short of the school's Minimum Mastery Criteria, particularly in the algebra chapter, specifically the topic of evaluating algebraic expressions. This occurs as a result of pupils' lack of understanding of variables and how to substitute variable values in algebraic forms. As a result, many students make mistakes when changing variable values, and their learning objectives are seen to be unfinished. The aim of this study was to determine whether using a differentiated learning model with the Teaching at the Right Level approach and algebraic block teaching aids improved the learning outcomes of class VIII students at SMP Negeri 25 Surabaya on the content on the value of algebraic forms. Using the Kemmis & McTaggart approach, this study is an example of classroom action research. The study's findings indicate that students are learning more about the importance of algebraic forms. The pre-cycle, cycle I, and cycle II learning completion rates for students were 14.7%, 64.7%, and 88.2%, respectively. This demonstrates how using a customized learning model in conjunction with algebraic block teaching aids and the Teaching at the Right Level strategy can enhance student learning outcomes.